Necrotizing Enterocolitis and Spontaneous Intestinal Perforation: A Spatiotemporal Case Cluster Analysis. Issue 1 (January 2019) - Murphy, Thomas; Yang, Samuel; Tucker, Richard; Collyer, Hillary; Kurkchubasche, Arlet G.; Bender, Jesse
Abstract : Objective: To expand existing statistical methods to identify clusters of necrotizing enterocolitis (NEC) and spontaneous intestinal perforation (SIP) cases in the neonatal intensive care unit. Methods: In an academic, tertiary referral center, possible NEC or SIP clusters were identified using a binomial distribution scan test. The incidence-density rate (IDR) was calculated as the number of cases per 1, 000 patient-days during each possible cluster and compared with the baseline IDR. A structured chart review compared cluster and noncluster cases. Spatial clustering analyzed the physical distribution of cases using the Grimson Test. Repeat analysis included only SIP cases. Result: The initial scan identified 3 suspected temporal clusters. IDR comparison confirmed only 1 cluster. Analysis of SIP only cases revealed similar results. Physical proximity was not a significant factor. Chart review of the SIP and NEC cases revealed significant increases during the confirmed cluster of small for gestational age infant births and indomethacin treatment. Chart review of the SIP only cases in the confirmed cluster revealed no significant differences. Conclusion: Statistical methods distinguish whether suspected case clusters represent a significant increase in baseline incidence. True clusters warrant detailed investigation including spatial analysis and chart review. This approach may have application in other disease processes and populations.